Modelling acoustic reflection loss at the ocean surface for small angles of incidence - Jones, A.; Duncan, Alec; Maggi, A.; Sendt, J.; Clarke, P. (2010)
This paper investigates the performance of available models of acoustic surface loss for small grazing angles of incidence, and for lower wind speeds for which bubble formation is less likely to play a role. In order to investigate the expected importance of shadowing for these scenarios, a wave-type model has been run with a deterministic simulation of the surface profile, for a number of situations for which transmission has been confined to small angle arrivals. This modelling includes, implicitly, the effects of diffraction into the shadowed regions, and the effects of the varying levels of intensity of insonification in accord with the different surface slopes. The surface loss values inferred from these simulations are compared with those from the other models, and to the extent possible, with the apparent effects observed with available at sea data. In this work, attention has been paid to the angles of incidence at the surface which dominate the loss effects. To the extent possible, conclusions are drawn on the apparent accuracy of the various models, and the need for further work to ascertain their appropriateness at small grazing angles. © 2010 CROWN.